The Active Ingredients Identification and Antidiarrheal Mechanism Analysis of Plantago asiatica L. Superfine Powder - Dong, Chun-Liu; Qin, Yue; Ma, Jin-Xin; Cui, Wen-Qiang; Chen, Xing-Ru; Hou, Li-Ya; Chen, Xue-Ying; God’spower, Bello-Onaghise; Eliphaz, Nsabimana; Qin, Jun-Jie; Guo, Wen-Xin; Ding, Wen-Ya; et al. (Frontiers in Pharmacology, 2021)
Plantago asiatica L. is a natural medicinal plant that has been widely used for its various pharmacological effects such as anti-diarrheal, anti-inflammatory and wound healing. This study aims to explore the anti-diarrheal active ingredients of Plantago asiatica L. that can be used as quality markers to evaluate Plantago asiatica L. superfine powder (PSP). Molecular docking experiment was performed to identify the effective components of Plantago asiatica L., which were further evaluated by an established mouse diarrhea model. Na+/K+-ATPase and creatine kinase (CK) activities and the Na+/K+ concentrations were determined. The gene expression of ckb and Atp1b3 were detected. PSP was prepared and evaluated in terms of the tap density and the angle of repose. The structures of PSPs of different sizes were measured by infrared spectra. The active ingredient contents of PSPs were determined by HPLC. The results indicated that the main anti-diarrheal components of Plantago asiatica L. were luteolin and scutellarein that could increase the concentration of Na+, K+ by up-regulating the activity and gene level of CK and Na+/K+-ATPase. In addition, luteolin and scutellarein could also decrease the volume and weight of small intestinal contents to exert anti-diarrheal activity. Moreover, as the PSP size decreased from 6.66 μm to 3.55 μm, the powder tended to be amorphous, homogenized and of good fluidity, the content of active compounds gradually increased, and the main structure of the molecule remained steady. The optimum particle size of PSP with the highest content of active components was 3.55 μm, and the lowest effective dose for anti-diarrhea was 2000 mg/kg. Therefore, the anti-diarrheal active ingredients of PSP were identified as luteolin and scutellarein that exert anti-diarrheal activity by binding with Na+/K+-ATPase. PSP was successfully prepared and could be used as a new dosage form for the diarrhea treatment.